FAIRCLOUGH’S THREE DIMENSION FRAMEWORK USED ON TRUMP’S POLITICAL SPEECH: A CRITICAL DISCOURSE ANALYSIS (A CASE STUDY OF HISTORIC SPEECH RELATED TO JERUSSALEM AS ISRAEL’S CAPITAL) - Dian Handayani; Heriyanto Heriyanto; Ypsi Soeria Soemantri (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The aim of this research is to analyze and find out the ways used by Trump in delivering his political speech, based on Fairclough’s three dimension framework (1995). The method applied in this research is descriptive qualitative method. The data in this research is a set of transcription extracted from Trump’s speech published on December 8th, 2017 on youtube, which theme of the speech is Trump’s statement about Jerussalem being the capital of Israel. The research uses Fairclough theory. Since there are three dimension frameworks of the critical discourse analysis; first, a text or description (speech, writing, vicual images or a combination of these). Second, a discursive pratice or interpretation which involves the production and consumption of the texts. Third, a social practice or explanation of the discourse. Based on the theory, this research found some results that had been gained from Trump political speech; The ways of delivering this speech were vocabulary, voice, mood and transitivity.  This speech conveyed meaning as persuading, criticism, constrastive participant, power, authority, allusion, claim, that were implicitly contained in this speech